The Developing Potential Model for Small and Medium Broiler Farm Industry Entrepreneurs for Self-reliance in Digital Economy - Noysumran, Somporn; Wisetsri, Worakamol; Attavinijtrakran, Preeda (Arts of Management Journal, 2022)
The purposes of this research were: 1) to investigate the components for developing potential model for broiler farm industry entrepreneurs, 2) to develop the potential model for broiler farm industry entrepreneurs, and 3) to create a development manual as the guideline for small and medium broiler farm industry entrepreneurs for self-reliance in digital economy. The samples were 9 entrepreneurs, executives, and broiler farm industry experts for an in-depth interview, 15 entrepreneurs, executives and scholars related to broiler farm industry for a focus group, five experts for evaluating the manual, and 402 entrepreneurs, executives and scholars related to broiler farm industry for a questionnaire. The study was a mixed method: qualitative and quantitative. The tools for the qualitative method were an in-depth interview and a focus group, and their data were analyzed by using content analysis. Then the qualitative method’s results were used to create a questionnaire. The data from the questionnaire were analyzed by using descriptive statistics frequency, means, standard deviation, and exploratory factor analysis. The research results showed that 1) the potential model for small and medium broiler farm industry entrepreneurs for self-reliance in digital economy were composed of three essential components : 1.Managing Farm Business, 2. Managing Resource, and 3. Managing Self, 2) these three components which were significantly co-related were used for the potential model for small and medium broiler farm industry entrepreneurs for self-reliance in digital economy and 3) a development manual as the guideline for small and medium broiler farm industry entrepreneurs for self-reliance in digital economy focused on continuing self-development. In conclusion, all experts agreed that the model and its manual’s appropriateness were high. Therefore, the model and the manual can be a guideline for developing potential of small and medium broiler farm industry entrepreneurs.